1998
DOI: 10.1002/(sici)1521-3765(19980615)4:6<1048::aid-chem1048>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Crystallization of Vaterite in Collagenous Matrices

Abstract: The influence of high supersaturation on kinetic control and the importance of the polypeptide structure in the crystallization of calcium carbonate polymorphs were studied in crosslinked gelatin films containing high concentrations of the polypeptides poly-l-aspartate and poly-l-glutamate. Oriented crystallization of vaterite occurs in uniaxially deformed gelatin films containing poly-l-aspartate at concentations greater than 100 mg per gram of gelatin. The fact that no orientation of the mineral phase was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 7 publications
6
108
0
Order By: Relevance
“…As an alternative to additive-directed crystallization, it is also becoming increasingly evident that the micro-environments in which crystals form can themselves define crystallization pathways and products. [15][16][17][18][19] Not only is this of particular importance to processes that naturally occur in confinement such as weathering, biomineralization and the manufacture of nanomaterials, but confinement can potentially provide a stand-alone means of controlling crystallization.…”
Section: Introductionsupporting
confidence: 66%
“…As an alternative to additive-directed crystallization, it is also becoming increasingly evident that the micro-environments in which crystals form can themselves define crystallization pathways and products. [15][16][17][18][19] Not only is this of particular importance to processes that naturally occur in confinement such as weathering, biomineralization and the manufacture of nanomaterials, but confinement can potentially provide a stand-alone means of controlling crystallization.…”
Section: Introductionsupporting
confidence: 66%
“…The influence of organic matter, exopolysaccharides and polyaspartate in the precipitation of vaterite can also be found in nature (Falini et al 1998;Gower and Tirrell 1998). Vaterite crystals similar to those obtained in this study have recently been found in Lake Issyk-Kul (Kyrgyzstan) and have been attributed to Synechococcus activity in mucilagenous mats containing polyaspartate (Giralt et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[8] A considerable amount of research on the processes occurring at the organic-inorganic interfaces and of calcium carbonates, related to the biomineralization or bioinorganic chemistry, has already been performed. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, the model studies on crystallization at the organic-inorganic interfaces, carried out in vitro, typically use the macromolecules extracted from biogenic crystals [15,[17][18][19][21][22][23][24][25][26][27][28][29][30] or synthetic macromolecules, [9,14,15,[31][32][33][34][35][36] which are considered to be their analogues. In addition, the experimental data indicate that the metastable modifications like ACC, are the first mineral phases that appear during the formation of shells, thus acting as a reservoir of constituting ions for subsequent formation of stable modifications.…”
Section: Introductionmentioning
confidence: 99%